(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2023)
Along with the apparel or clothing industry, diversified uses of natural lignocellulosic fibre are getting popularity in many fields e.g., composites, automotive, marines, aerospace, electronics, civil construction, nanotechnology, biomedical, etc. The property and uses of textiles are determined by their constituent fibre properties. The proximate composition and thermogravimetric analysis (TGA) data of a total of 9 local hemp and flax genotypes (3 and 6, respectively) were carried out to understand their suitability in different applications. A wide variation was observed in the ash content of hemp and flax fibres varied from 1.7 to 17.7%, crude protein 3.27 to 9.02%, crude fibre 26.51 to 55.32%, ether extract 2.6 to 20.9% and energy value 284.44 to 383.96 kcal 100–1 g. In TGA analysis, all the fibres showed a similar trend. The flax genotypes contain lower ash and ether extract and higher DM, crude carbohydrate and crude fibre than hemp genotypes. Therefore, flax could be used in the lightweight composite, textile, pulp and cellulose-based industries. The hemp fibre had higher ash which was reflected by a higher residue at 500oC in TGA analysis. To understand the viability of these flax fibres, further investigations are needed. Bangladesh J. Sci. Ind. Res. 58(1), 65-70, 2023